PENGEMBANGAN MEDIA KONKRET BERBENTUK VELG RUJI ENERGI UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR - Endaryati, Sri Adhi (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2023)
Science subjects at the elementary level are often considered difficult because of the amount of material that students must read and understand. Therefore, researchers conducted media development that was able to foster student motivation towards science learning. Concrete media